2020
DOI: 10.1016/j.devcel.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Germ Cells and Development

Abstract: The animal germline is an immortal cell lineage that gives rise to eggs and/or sperm each generation. Fusion of an egg and sperm, or fertilization, sets off a cascade of developmental events capable of producing an array of different cell types and body plans. How germ cells develop, function, and eventually give rise to entirely new organisms is an important question in biology. A growing body of evidence suggests that phase separation events likely play a significant and multifaceted role in germ cells and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 145 publications
(238 reference statements)
1
68
0
Order By: Relevance
“…Nuages are membraneless electron-dense cytoplasmic condensates. It has been suggested that nuage in germ cells may form via liquid-liquid phase separation [ 63 ]. Notably, DDX4, an essential factor for piRNA biogenesis, undergoes phase separation both in vitro and in cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuages are membraneless electron-dense cytoplasmic condensates. It has been suggested that nuage in germ cells may form via liquid-liquid phase separation [ 63 ]. Notably, DDX4, an essential factor for piRNA biogenesis, undergoes phase separation both in vitro and in cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The switch-like decisions during germ cell development are proposed to be closely related to the formation of large protein complexes, including large granules, also known as membraneless organelles (for review [47,48]). In this regard, new ideas about the cotranslational assembly of multisubunit protein complexes with the participation of a chaperone, based on rigorous experiments, are of particular interest [2,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane‐less granules have been found to display specialized behaviors more readily observable in in vitro LLPS assemblies such as fusion, fission, wetting, shearing, dynamicity, and so forth (Banani et al, 2017; Dodson & Kennedy, 2020) (Box 1). Notably, the endoplasmic reticulum (ER) has been demonstrated to be capable of acting as an anchorage for membrane‐less organelles through specialized contact‐sites and exert limited regulatory control over assembly and fission of SGs and PBs (Lee et al, 2020).…”
Section: Rnp Granulesmentioning
confidence: 99%